Caribbean Region. Annual report 2008 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
This report consolidates the national reports that have been presented for 2008, and is reinforced by the results of programs, projects and interventions. IICA's programs in the Caribbean Region continue to respond to the Key Binding Restrictions identified in the Jagdeo Initiative and, through some of its programs, the Institute has made the public aware of the process of repositioning agriculture in the Caribbean.